Self-assembled nanomaterials based on beta (β3) tetrapeptides. (24th February 2016) - Seoudi, Rania S; Hinds, Mark G; Wilson, David J D; Adda, Christopher G; Del Borgo, Mark; Aguilar, Marie-Isabel; Perlmutter, Patrick; Mechler, Adam
Abstract: β 3 -amino acid based polypeptides offer a unique starting material for the design of self-assembled nanostructures such as fibres and hierarchical dendritic assemblies, due to their well-defined helical geometry in which the peptide side chains align at 120° due to the 3.0–3.1 residue pitch of the helix. In a previous work we have described the head-to-tail self-assembly of N-terminal acetylated β 3 -peptides into infinite helical nanorods that was achieved by designing a bioinspired supramolecular self-assembly motif. Here we describe the effect of consecutively more polar side chains on the self-assembly characteristics of β 3 -tetrapeptides Ac- β 3 Ala- β 3 Leu- β 3 Ile- β 3 Ala (Ac-β 3 [ALIA]), Ac- β 3 Ser- β 3 Leu- β 3 Ile- β 3 Ala (Ac-β 3 [SLIA]) and Ac- β 3 Lys- β 3 Leu- β 3 Ile- β 3 Glu (Ac-β 3 [KLIE]). β 3 -tetrapeptides complete 1 1/3 turns of the helix: thus in the oligomeric form the side chain positions shift 120° with each added monomer, forming a regular periodic pattern along the nanorod. Dynamic light scattering (DLS) measurements confirmed that these peptides self-assemble even in highly polar solvents such as water and DMSO, while diffusion-ordered NMR spectroscopy revealed the presence of a substantial monomeric population. Temperature dependence of the size distribution in DLS measurements suggests a dynamic equilibrium between monomers and oligomers. Solution casting produced distinct fibrillar deposits after evaporating the solvent. In the case of the apolar Ac- β 3 [ALIA] the longitudinal helix morphology gives rise to geometrically defined (∼70°) junctions between fibres, forming a mesh that opens up possibilities for applications e.g. in tissue scaffolding. The deposits of polar Ac- β 3 [SLIA] and Ac- β 3 [KLIE] exhibit fibres in regular parallel alignment over surface areas in the order of 10 μ m.